1986
DOI: 10.2170/jjphysiol.36.451
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-independent, hydrogen ion-dependent changes in membrane potential and conductance induced by dipeptides in Triturus enterocytes.

Abstract: The effects of Na+ and pH in the medium on dipeptide transport across Triturus small intestinal brush border membrane were studied electrophysiologically. Although glycylglycine exists mainly in the zwitterionic form at pH 7.30, it induced marked depolarization in the membrane potential and reduction in the input resistance both in the presence and absence of Na+ in the medium. Similar Na + -independent depolarization and resistance change were also observed with L-carnosine. On the contrary, glycine induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Na+-independent and pH-dependent electrical responses to dipeptides in amphibian small intestines were also demonstrated * Present address: Second Department of Internal Medicine, Faculty of Medicine, University of Tokyo, Tokyo 113, Japan. (Shimada & Hoshi, 1986a;Hoshi, 1986). As the transport of intact di-and tripeptides across the brush-border membrane has an important physiological role in the intestinal absorption of protein hydrolysates (Adibi & Kim, 1981), the H+ gradient across the brush-border membrane has attracted the renewed attention of investigators.…”
Section: Introductionmentioning
confidence: 99%
“…Na+-independent and pH-dependent electrical responses to dipeptides in amphibian small intestines were also demonstrated * Present address: Second Department of Internal Medicine, Faculty of Medicine, University of Tokyo, Tokyo 113, Japan. (Shimada & Hoshi, 1986a;Hoshi, 1986). As the transport of intact di-and tripeptides across the brush-border membrane has an important physiological role in the intestinal absorption of protein hydrolysates (Adibi & Kim, 1981), the H+ gradient across the brush-border membrane has attracted the renewed attention of investigators.…”
Section: Introductionmentioning
confidence: 99%
“…In these vesicles, glycyl-dipeptides, such as Gly-Pro, Gly-Sar and Gly-Gly, have been shown to cause depolarization of the membrane potential which can be visualized by a change in fluorescence of a membrane potential-sensitive dye, such as diS-C3-(5), added to the suspension medium (Ganapathy et al 1984;Takuwa et al 1985a, b). Also, Boyd & Ward (1982) and Shimada & Hoshi (1986) demonstrated that the transmembrane potential across the luminal membrane of intact amphibian intestinal epithelia was depolarized when dipeptides, such as Gly-Leu, Gly-Gly and carnosine, were added to Na+-free mucosal bathing solution, and that the depolarization was accompanied by a reduction of the input resistance. The pHo dependence of the amplitude of the depolarization was demonstrated by the latter authors (Shimada & Hoshi, 1986 In the present study, the coupling ratio of H+ current to dipeptide flux was determined to be approximately 2 (1P78 + 0-12).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Boyd & Ward (1982) and Shimada & Hoshi (1986) demonstrated that the transmembrane potential across the luminal membrane of intact amphibian intestinal epithelia was depolarized when dipeptides, such as Gly-Leu, Gly-Gly and carnosine, were added to Na+-free mucosal bathing solution, and that the depolarization was accompanied by a reduction of the input resistance. The pHo dependence of the amplitude of the depolarization was demonstrated by the latter authors (Shimada & Hoshi, 1986 In the present study, the coupling ratio of H+ current to dipeptide flux was determined to be approximately 2 (1P78 + 0-12). A linear relationship between H+ and Gly-Gly influxes supports the idea that Gly-Gly transport is mediated by an H+-coupled co-transport, similar in mechanism of energy coupling to the Na+-coupled transport of D-glucose and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The depolarizing responses were shown to be associated with an increase in membrane conductance. Both the depolarization and membrane conductance increase were independent of the presence of Na+ in the medium (2,18) . Lowering pH of the mucosal perfusion solution caused augmentation of the depolarizing response to dipeptides (18) .…”
Section: Electrophysiology Of the Peptide Transportmentioning
confidence: 90%
“…Both the depolarization and membrane conductance increase were independent of the presence of Na+ in the medium (2,18) . Lowering pH of the mucosal perfusion solution caused augmentation of the depolarizing response to dipeptides (18) . Alkalinization of the perfusion solution resulted in the reverse change (diminution of the amplitude) even when the concentration of zwitterion dipeptide was made equal to that in control.…”
Section: Electrophysiology Of the Peptide Transportmentioning
confidence: 90%